The Effectiveness of Social Assistance in Handling Covid-19 - Arif Setyawan (Ridwan Institute, 2023)
The background for conducting this research is that there are problems with effectiveness, obstacles and efforts in optimizing the distribution of social assistance in handling Covid-19 in the Administrative City of North Jakarta. The purpose of this research is to find out and analyze the effectiveness, obstacles and efforts in optimizing the distribution of social assistance in handling Covid-19 in the Administrative City of North Jakarta. This research method is included in the type of post-positivism research that uses a qualitative approach with a total of 10 informants. Data analysis techniques in this study are data reduction, data presentation and conclusion and verification. The results of this study prove that: (1) The process of distributing social assistance in the form of groceries and BLT in handling Covid-19 in the Administrative City of North Jakarta, is still not effective. Many people who should have received assistance were not even recorded because data manipulation in the field was carried out by appointed implementing officers. (2) Obstacles encountered in the process of distributing social assistance in handling Covid-19 in the Administrative City of North Jakarta, include the lack of outreach to the public about the procedures and requirements for receiving social assistance, the lack of precise targets in the provision of social assistance, and recorded data on recipients of social assistance in DTKS (Integrated Social Welfare Data) is less valid. (3) Efforts made to optimize the effectiveness of the distribution of social assistance in handling Covid-19 in the Administrative City of North Jakarta, by increasing the budget for the procurement of social assistance so that the number of beneficiaries can be greater, strengthens the synergy between the Central Bureau of Statistics and the Ministry of Social Affairs in making population database on the basis of a Population Identification Number, as well as the formation of an integrated team and socialization of the timing of assistance in the implementation of social assistance distribution so that it becomes an example for other regions.